Pemanfaatan Rosin (Gondorukam) - Hayat S (Balai Besar Kimia dan Kemasan, 1987)
Rosin is residue from distillation process pine gum, extraction pine stump wood. It was get by product pulp industry form rosin tall oil. Rosin is a complex mixture of mainly resin acids and a small amount of nonacidic component. it can be reacted with metal hydroxide namely calcium hydroxide, zinc hydroxide, aluminium hydroxide and sodium hydroxide.